From preventive cardiology to non-communicable disease prevention in Russia - S. A. Boytsov; R. G. Oganov (Российский кардиологический журнал, 2013)
The increase in cardiovascular morbidity and mortality in the second half of the 20th century was mainly determined by the lifestyle and lifestyle-associated risk factors (RF). Russian epidemiologic and preventive studies, performed by the USSR Research Cardiology Centre (USSR Academy of Medical Sciences) and the State Research Centre for Preventive Medicine (Russian Ministry of Health), assessed the RF prevalence across different country regions, evaluated the RF input in the development of cardiovascular disease (CVD), and provided the evidence base for the strategies and policies on prevention of CVD and other non-communicable diseases. The decrease in Russian CVD mortality has been facilitated by the implementation of the National Project “Health”, the Federal Target Programme “Social disease prevention and control”, and a range of other legislative measures. Future studies should be focused on the epidemiology of CVD and other noncommunicable diseases across climatic and geographical regions; the role of influenza and acute respiratory diseases in CVD incidence; genetic RF; cardiovascular risk markers, including metabolomic and lipidomic markers; meta-genetic studies; vascular ageing; and vaccination for CVD prevention.